PERLINDUNGAN HUKUM TERHADAP ANAK DAN PEREMPUAN SELAKU KORBAN KEJAHATAN SEKSUAL - Rismando Sitepu, Antonius Prananta; Rahmayanti, Rahmayanti; Pohan, Masitah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This research aims to analyze the problems in the legal protection of children and women victims of sexual crimes in Indonesia. This research uses normative juridical research method with data collected through literature study of laws and regulations, legal literature, and previous research related to protection and children. The analysis was conducted qualitatively to assess the compatibility between the applicable legal norms and their implementation in the community. The results showed that although the legal framework is quite comprehensive, there are significant challenges in the implementation of legal protection, including overlapping and incompatible regulations, lack of socialization and understanding of the law, slow handling and lenient sentences, lack of supporting facilities and resources, and social and cultural barriers. This research recommends strengthening institutional capacity, improving victim-friendly integrated services, and legal education and socialization to increase awareness and protection of children and women as victims of sexual crimes. A multi-disciplinary and collaborative approach is considered crucial to overcome problems in the current legal protection.